CREEP RELIABILITY ANALYSIS OF TURBINE BLISK BASED ON DUAL RESPONSE SURFACE METHOD - ZHANG ChunYi; WANG AiHua; SUN Tian; JING HuiZhe; LI ChengWei (Jixie qiangdu)
To more accurately and effectively solve the problem of comprehensive reliability of multi-failure mode with the thermal creep, dual response surface method（DRSM） was adopted to implement the reliability of aero-engine turbine blisk. The numerical characteristics of the material parameters were obtained through the creep test data. The gas temperature, material density, elastic modulus and working rotation speed of the blisk structure were select as input variables. By constructing the finite element model of the blisk and the thermal-structural coupling analysis method, the stress and strain of turbine blisk were obtained. The mathematical model of dual response surface for stress and strain of turbine blisk was established by using the Latin hypercube small sampling technique. The comprehensive reliability analysis of the blisk was completed by using Monte Carlo method with linkage sampling of dual response surface model. The results indicate that the comprehensive reliability of blisk with thermal creep is 0.985 6. The comparison of method shows that dual response surface method can significantly improve computational efficiency without the loss of accuracy.